Method for improving the wear resistance of a component and component

By thermally spraying the deposited molybdenum layer on the surface of the mechanical components and contacting the aqueous solution at high temperatures, the friction wear and jamming of the mechanical components in high temperature environments is solved, and significant wear resistance is achieved.

CN110004400BActive Publication Date: 2025-03-25AIRBUS OPERATIONS (SAS)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201811469678.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-29
Filing Date
2018-11-28
Publication Date
2025-03-25
Estimated Expiration
2038-11-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the wear resistance of mechanical components, especially in high temperature environments, which lead to friction wear and jamming problems that are difficult to solve.

Method used

The layer containing molybdenum is deposited by thermal spray and contacted with the aqueous solution at a temperature above room temperature to form a porous structure to improve wear resistance.

Benefits of technology

It significantly reduces the friction coefficient, improves the wear resistance of mechanical components, reduces sliding wear and jamming, and remains stable under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110004400B_ABST
    Figure CN110004400B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for improving the wear resistance of a component, comprising the steps of: (a) depositing a layer comprising molybdenum on all or part of the surface of the component by thermal spraying; (b) contacting the surface of the component presenting the layer comprising molybdenum with an aqueous solution at a temperature above room temperature. The invention also relates to a component treated according to this method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface treatment.

[0002] More specifically, it is an object of the present invention to provide a method for treating a component in a durable manner in order to modify its wear properties and in particular its mechanical wear properties.

[0003] The invention also relates to the mechanical parts thus treated. Background Art

[0004] Many technical fields use complex mechanisms in which the movement of components relative to each other creates wear problems that can affect the reliability and durability of these components.

[0005] Therefore, in the aeronautical field, the hinged connection between the engine and the tower part operating at high temperatures is provided by a component comprising a ball joint, a shaft and a ring.

[0006] The ball joint system generally comprises a female part and a spherical part carried by a shaft. The spherical part to be fitted into the female part undergoes rotational movement in all directions so that the surface of the spherical part and the surface of the female part are in permanent friction against each other.

[0007] In the case of ball joint systems and other similar systems, two types of friction wear are distinguished. The first of these types, called "fretting wear", involves friction of very low amplitudes, usually of the order of a few micrometers. Fretting wear occurs between two surfaces of the same kind or of different kinds, which are in contact with one another and are subjected to oscillating movements of the microvibration type, with sufficiently low amplitudes, so that only partial sliding of the contact occurs. The second type of friction wear corresponds to sliding wear, where the amplitude of the movements can reach several tens of millimeters.

[0008] Frictional wear develops from the microscopic asperities that appear on the friction surfaces that are in contact and tend to come together. When the locally applied loads are high and in the case of materials of similar composition on the two friction surfaces, friction leads to surface wear and surface degradation, which can even lead to the seizure of the shaft or ball joint. In addition, when the environment of the hinge connection has high temperatures, in particular between 300°C and 650°C, this promotes the appearance of adhesive wear, which is the ultimate cause of seizure.

[0009] Various methods for improving the wear resistance of friction surfaces are known in the prior art.

[0010] For example, there are surface treatments for improving the durability of the friction surfaces of titanium alloys and for reducing the wear index. The treatments may consist in depositing a coating of titanium nitride, or other thermochemical treatments based on the diffusion of nitrogen, allowing the formation of mixed compounds of the TiN and Ti2N type several micrometers thick on the surface of the titanium alloy parts. However, these treatments are limited to titanium alloy surfaces and are not very suitable for systems of the ball joint type. Moreover, these treatments do not significantly reduce the phenomena of sliding wear and seizure.

[0011] Patent application FR3042563 filed in the name of Airbus Operations S.A. and published on April 21, 2017, proposes a friction adaptation interface between two parts made of nickel, nickel alloys or cobalt-chromium alloys. This interface involves two adaptation layers, each of which is deposited on one of the two parts. The first of these adaptation layers is a microporous layer of an alloy of cobalt, chromium, molybdenum and silicon, but the second adaptation layer obtained by a thermochemical treatment of carbon diffusion on the surface of the second part interacts with the first adaptation layer so as to form an oxide layer on the first adaptation layer. Although this adaptation interface can significantly reduce adhesive wear caused by friction at operating temperatures between 300° C. and 650° C., it is only applicable to parts made of nickel, nickel alloys or cobalt-chromium alloys and requires two separate treatments for each of the two parts in contact.

[0012] We can also mention the use of organic resins to improve wear resistance, which are usually applied in liquid form before curing and are therefore in the form of a lubricating film, which must show certain characteristics, in particular at the level of the coefficient of friction. The organic resin must be small in thickness, stable and strong. In fact, in all relevant fields, and in particular in the aviation field, the organic resin film used to reduce wear between moving parts must have a very small thickness so as not to interfere with the operating principle of the device. The presence of the organic resin film must not lead to contamination of the mechanism or environment, for example due to excessive vapor pressure, outgassing phenomena or the flow of liquid. In addition, the organic resin must have a high stability to ensure the maintenance of friction properties and to limit the development of contamination phenomena by means of the formation of degradation by-products, at a time that matches the period during which it is impossible to maintain the moving parts. The organic resin must also have a very high durability relative to the aggressive environment.

[0013] The invention has the object of proposing a method that is easy to implement and that makes it possible to improve the wear properties of any system in which the movement of two parts relative to each other creates wear problems, whatever the materials of the two parts and whatever the operating temperature. Summary of the invention

[0014] To this end, the present invention proposes a method for improving the wear resistance of a component, the method comprising the following steps:

[0015] a) depositing a layer comprising molybdenum by thermal spraying on all or part of the surface of the component;

[0016] b) contacting the surface of the component having the layer comprising molybdenum with an aqueous solution at a temperature above room temperature.

[0017] The method according to the present invention has at least one of the following optional features alone or in combination.

[0018] The surface of the component to be treated is made of a material selected from the group consisting of titanium alloy, nickel alloy and austenitic stainless steel.

[0019] The components to be treated are selected from the group consisting of components of ball joint systems, piston rods, rings, gears, camshafts, valves, injection pumps, bearing housings, bearings and shafts.

[0020] In step (a) of the method according to the invention, the thermal spraying used is plasma spraying.

[0021] In step (a) of the method according to the invention, the layer deposited by thermal spraying comprises predominantly molybdenum.

[0022] In step (b) of the process according to the invention, the aqueous solution comprises only water.

[0023] In step (b) of the process according to the invention, the aqueous solution comprises at least one further element besides the solvent.

[0024] In step (b) of the process according to the invention, the contacting is carried out in static mode or in dynamic mode.

[0025] In step (b) of the process according to the invention, the contacting has a duration of between 1 hour and 54 hours and in particular between 5 hours and 48 hours.

[0026] Prior to step (a), the method according to the present invention has a step or a processing step of sandblasting the surface.

[0027] The invention also relates to a component on the whole or part of whose surface a layer comprising molybdenum is deposited, the component then being hydrated at a temperature above room temperature according to the method defined above. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The variation of the coefficient of friction as a function of the number of cycles applied to a component according to the method of the invention, ie a component whose surface was coated with a layer comprising molybdenum and then hydrated at a temperature greater than or equal to 40° C., is shown.

[0029] Figure 2Shown for comparison is the variation of the coefficient of friction as a function of the number of cycles applied to a component whose surface is coated with a layer comprising molybdenum but is not hydrated at a temperature greater than or equal to 40° C.

[0030] Figure 3 Shown for comparison is the variation in the coefficient of friction as a function of the number of cycles applied to a component whose surface is coated with a layer comprising molybdenum and then with an organic resin layer. DETAILED DESCRIPTION

[0031] The present invention proposes a two-step treatment method, and only the first step requires equipment suitable for thermal spraying, especially plasma spraying. Because the second step is hydration at a moderate temperature, that is, above room temperature, the second step is very easy to carry out.

[0032] The positive combination of the deposition treatment of the molybdenum-containing layer and the hydration can significantly improve the wear resistance of the mechanical part. Since the hydration maintains the porosity of the molybdenum-containing layer, the second treatment corresponding to the hydration maintains the improvement in wear resistance provided by the molybdenum-containing layer. Other known treatments such as the deposition of organic resins will have the opposite effect: they eliminate the improvement provided by the molybdenum-containing layer.

[0033] Furthermore, the active combination of the deposition process of the molybdenum-containing layer and the hydration does not change the corrosion resistance of the treated component or even improves the corrosion resistance of the treated component.

[0034] Finally, the two-step treatment method can be used on all machine parts without any restrictions on the materials they are composed of and the temperatures at which these machine parts are used.

[0035] Therefore, the present invention relates to a method for improving the wear resistance of a component, comprising the following steps:

[0036] a) depositing a layer comprising molybdenum by thermal spraying on all or part of the surface of the component; and

[0037] b) contacting the surface of the component having the layer comprising molybdenum with an aqueous solution at a temperature above room temperature.

[0038] By "improvement of wear resistance" is meant that a component according to the method of the invention, i.e. a component having at least one region of its surface provided with a layer comprising molybdenum and hydrated at a temperature above room temperature, has improved wear resistance relative to an identical but untreated component.

[0039] "Room temperature" refers to a temperature of 22°C ± 5°C. Thus, "above room temperature" refers to a temperature above 27°C.

[0040] An "untreated part" is a part that has neither been coated with a layer comprising molybdenum nor hydrated at a temperature above room temperature. This improvement can be demonstrated or quantified by techniques familiar to a person skilled in the art, such as measuring the value of the coefficient of friction.

[0041] In general, the value of the coefficient of friction is measured in the presence of a lubricant between two parts that slide, roll or rotate relative to each other. Any lubricant commonly used in the aerospace field can be used for this purpose. As a specific example of such a lubricant, we can mention lithium-based lubricants, and in particular lubricants that include (i) synthetic oils based on hydrocarbons and esters and thickened by lithium complexes, (ii) oxidation and corrosion inhibitors and (iii) load-bearing additives. An example of such a lubricant is the product produced by Shell .

[0042] The values ​​of the coefficient of friction are measured with a base specimen of the type having a pin sliding on a rail in the presence of a lubricant, in particular as described above.

[0043] Under identical operating conditions, the coefficient of friction of the parts treated according to the method of the invention is reduced relative to the coefficient of friction obtained for untreated parts.

[0044] Furthermore, it should be noted that, under the same operating conditions, the coefficient of friction of the component treated according to the method of the invention is reduced relative to the coefficient of friction obtained for a component subjected only to step (a) of the method of the invention, i.e. a component having at least one surface area with a layer comprising molybdenum but without hydration. Thus, under the operating conditions as defined in the experimental part below, the coefficient of friction of the component treated according to the method of the invention is reduced by at least 5% and in particular by at least 10% relative to the coefficient of friction obtained for a component subjected only to step (a) of the method of the invention, i.e. a component having at least one surface area with a layer comprising molybdenum but without hydration.

[0045] The present invention is applicable to any component, the surface of which, when in contact with a second component, may be subject to at least one of the two types of wear, namely fretting wear or sliding wear, through the above-mentioned friction.

[0046] In the sense of the present invention, a "surface" is understood to be the outer part of an object or solid which limits the object or entity in all directions. For the same object (or entity), different surfaces can be conceptually defined. The present invention is applicable to any type of surface, regardless of its geometry. The latter can be simple, such as a completely flat surface, or more complex, such as a concave or convex surface, regardless of the material that makes up the surface and the rest of the components on which it depends.

[0047] In the case of the present invention, the surface of the part to be treated, i.e., the surface of the part whose wear resistance is to be improved, can be an inorganic surface, an organic surface such as a resin surface, or a composite material surface such as a composite material with an organic matrix, a composite material with a ceramic matrix, or a composite material with a metal matrix.

[0048] In particular, when the surface of the component to be treated is an inorganic surface, the latter may be a surface of a conductive material, a semiconductive material and / or an insulating material.

[0049] Among the conductive materials used in the invention, we can mention metals, noble metals, oxidized metals, transition metals, metal alloys and in particular, by way of non-limiting example, nickel, zinc, gold, platinum, titanium, steel mixtures and alloys thereof. More specifically, the surface of the part to be treated is made of a material chosen from a titanium alloy such as the alloy known as TA6V, which is an alloy comprising titanium, 6 wt% of aluminum and 4 wt% of vanadium, for example Nickel alloys and austenitic stainless steel titanium alloys.

[0050] In the context of the present invention, the components to be treated can be selected from spherical joint system components such as balls or ball joints, piston rods, rings such as sealing rings, gears, camshafts, valves, injection pumps, bearing housings, bearings and shafts.

[0051] In the context of the present invention, the components to be treated may be of any size and shape. A particular feature of the method according to the present invention is that it can be used both on small and large components.

[0052] The first step (step (a)) of the method according to the invention consists in depositing a layer comprising molybdenum on the component to be treated by thermal spraying.

[0053] Any thermal spraying technique can be used in the context of the present invention. It is particularly selected from the group comprising torch spraying, arc spraying, ultrasonic flame spraying and plasma spraying.

[0054] The thermal spraying used in step (a) of the method according to the invention is plasma spraying.

[0055] Plasma spraying, also known as "plasma spraying", is a thermal coating method that involves introducing particulate material into a plasma stream, where the particles melt and accelerate before they impinge on the surface to be coated. Plasma spraying thus makes it possible to obtain high-quality coatings by combining a high-energy, high-temperature heat source with a relatively inert spray medium (plasma gas) and high-velocity particles.

[0056] Step (a) of the method according to the invention can be carried out under ambient air (which is hereinafter referred to as the APS method, for "air plasma spray") or in a chamber containing a neutral gas. In the latter case, the method used depends on the specific conditions existing in the chamber, and the method can be designated as the LPPS method for "low pressure plasma spray", the IPS method for "inert plasma spray" or the ATC PS method for "atmosphere and temperature controlled plasma spray".

[0057] Various types of plasma gases are known that can be used in the plasma spraying according to step (a) of the present invention, and these plasma gases are in particular selected from oxygen, propane, helium, argon, hydrogen, xenon, neon, krypton and mixtures thereof. "Mixture" refers to both binary mixtures such as a mixture of argon and hydrogen, a mixture of oxygen and propane or a mixture of argon and helium, and ternary mixtures such as a mixture of helium, argon and hydrogen.

[0058] Typically, the part is fixed and centered on a turntable rotated by a motor so that its surface is to be coated. As a variant, the part to be coated can be moved in translation by a motor. Coolers positioned at the periphery of the part ensure that the temperature of the part remains constant and close to room temperature to avoid deformation of the part or degradation of its mechanical properties.

[0059] In a first embodiment of step (a) of the method according to the invention, the layer mainly comprises molybdenum. "Mainly" means that the proportion by weight of molybdenum relative to the total weight of the layer is greater than or equal to 70%. The weight of molybdenum relative to the total weight of the layer may be greater than or equal to 80%, typically greater than or equal to 90%, particularly greater than or equal to 95%, particularly greater than or equal to 96%, more particularly greater than or equal to 97%, even more particularly greater than or equal to 98%, or even greater than or equal to 99%. The other elements optionally present are elements of additions and / or impurities, the total amount of which, expressed by weight, is less than or equal to 30% relative to the weight of the layer comprising molybdenum. The total amount by weight of the other elements is less than or equal to 20%, typically less than or equal to 10%, particularly less than or equal to 5%, particularly less than or equal to 4%, more particularly less than or equal to 3%, even more particularly less than or equal to 2%, or even less than or equal to 1%, relative to the total weight of the layer.

[0060] In a second embodiment of step (a) of the method according to the invention, the layer is a layer of a molybdenum alloy and in particular an alloy of molybdenum and copper.

[0061] After step (a) of the method according to the invention, all or part of the surface of the component to be treated is coated with a layer comprising molybdenum, said layer being porous, having pore sizes in the micrometer range.

[0062] Typically, the thickness of the layer is between 100 μm and 2 mm, in particular between 110 μm and 1 mm, in particular between 120 μm and 700 μm. In order to achieve said thickness of the layer comprising molybdenum, that is to say after step (a) of the method according to the invention and before step (b) of the method according to the invention, it may be necessary to subject the layer to a treatment which reduces its thickness, such as grinding, grinding or machining.

[0063] The second step (step (b)) of the method according to the invention consists in hydrating the surface of the component coated with the layer comprising molybdenum. The hydration is carried out in the presence of an aqueous solution and at a temperature above room temperature.

[0064] The solution used in step (b) of the method according to the invention comprises water as a solvent, thus justifying the naming of the aqueous solution. "Water" refers to tap water, deionized water, distilled water or ultrapure water (18.2 MΩ). The solution used in step (b) of the method according to the invention can be a neutral, acidic or alkaline aqueous solution. If necessary, those skilled in the art will be able to determine the most suitable pH and therefore modify the pH of the aqueous solution.

[0065] Typically, the aqueous solution used in step (b) comprises only water. As a variant, the aqueous solution may comprise at least one other element in addition to the solvent. Any component that can improve certain properties of the coated parts or can accelerate or promote the method according to the present invention may be present in the aqueous solution used in step (b). As an example of another component, we can mention corrosion inhibitor additives and oxidation inhibitor additives. As a more specific example of another component, we can mention one selected from the group consisting of fluorinated compounds, stannate-based compounds, molybdate-based compounds, silicate-based compounds, cerium (III)-based compounds, phosphate-based compounds, (di)chromate-based compounds, cobalt-based compounds, carboxylate-based compounds, sulfite-based compounds and mixtures thereof.

[0066] In a first embodiment, step (b) comprises preparing an aqueous solution as defined above at a temperature T above room temperature and then bringing this solution into contact with the surface of the component having the layer comprising molybdenum and keeping the whole at temperature T.

[0067] In a second embodiment, step (b) comprises preparing an aqueous solution as defined above at room temperature and then bringing this solution into contact with the surface of the component having the layer comprising molybdenum and with a bulk temperature T greater than or equal to room temperature.

[0068] A temperature T, called "processing temperature", is assumed to have been reached when measurement of the temperature of the aqueous solution, carried out using a suitable metering device (eg a thermometer or a thermocouple), gives a value close to the desired temperature within the measurement uncertainty, typically for 15 minutes.

[0069] In the case of the present invention, the treatment temperature is above 30°C, in particular above 40°C, typically between 40 and 98°C, in particular between 60 and 97°C and, more particularly, between 80 and 95°C.

[0070] In the method according to the invention, the surface of the component having a layer comprising molybdenum can be brought into contact with the aqueous solution by any means that allows uniform hydration of the surface of the component having a layer comprising molybdenum. Thus, the contacting in step (b) can be carried out in static mode or in dynamic mode.

[0071] In the "static mode", also known as "batch mode", the surface of the component having the layer comprising molybdenum and usually the component is immersed and maintained in an aqueous solution, which is optionally agitated. Any agitation to which the aqueous solution is subjected can be mechanical agitation, magnetic agitation or agitation by ultrasound. For this purpose, a mixer, stirrer, magnetic bar, ultrasonic cleaner or homogenizer can be used.

[0072] In the "dynamic mode", also referred to as "column mode", the aqueous solution flows over the surface of the component having the layer comprising molybdenum.

[0073] The contact between the surface of the component having the layer containing molybdenum and the aqueous solution is carried out for less than 96 hours, in particular less than 72 hours and in particular less than 60 hours. Advantageously, the contact has a duration between 1 hour and 54 hours and in particular between 5 hours and 48 hours.

[0074] In the case of the method according to the invention and more particularly during the contacting step, when the contacting step is carried out in static mode, it may be necessary to permanently replenish the volume of the aqueous solution with water in order to compensate for the evaporation caused by the treatment temperature. Any device that can maintain a substantially constant volume of the aqueous solution, in particular by condensation of steam (reflux installation), can advantageously be used.

[0075] Furthermore, in the case of the method according to the invention and more specifically during the contacting step, it is necessary to keep the temperature of the aqueous solution at the treatment temperature as defined above. For this purpose, the contacting is carried out in the presence of a heating element and a temperature regulating device capable of keeping the heating element at a set temperature selected so that, when the set temperature is reached and maintained, the temperature of the aqueous solution remains at the treatment temperature.

[0076] At the end of the method according to the invention, i.e. when the time of contact between the surface of the component having the layer comprising platinum and the aqueous solution has elapsed, the surface may be rinsed. This rinsing step notably makes it possible to remove other elements that may be present in the aqueous solution in addition to the solvent as defined above. This rinsing is generally carried out using a solvent that is the same as that of the aqueous solution. Once the surface of the component having the layer comprising platinum has been rinsed, it is left to dry in a clean environment to prevent any solid or liquid contamination of the surface of the treated component.

[0077] If the contacting is carried out in static mode, the surface of the component having the layer comprising molybdenum and therefore the component is removed from the aqueous solution and then washed by immersing it in a washing solution or by letting the washing solution flow over the surface. If the contacting is carried out in static mode, the aqueous solution flowing over the surface of the component having the layer comprising molybdenum is replaced by the washing solution.

[0078] According to the method of the invention, optionally before carrying out step (a), there may be a step for preparing the component and promoting the adhesion of the molybdenum-based layer on the surface of the component to be treated, in particular by increasing the adhesion of the molybdenum-based layer by mechanical fixing and / or by increasing the roughness of the surface to be coated. The step may include a step of sandblasting the surface, i.e. a step of spraying with an abrasive, or a machining step.

[0079] The invention also relates to a component having a layer comprising molybdenum deposited on all or part of its surface according to a method as defined above and then hydrated at a temperature above room temperature.

[0080] All of the above descriptions of the method apply mutatis mutandis to the component according to the invention.

[0081] Other characteristics and advantages of the invention will become more apparent on reading the examples given below, for illustrative and non-limiting purposes.

[0082] I. Treatment according to the invention

[0083] I.1. Step of depositing a layer comprising molybdenum

[0084] A component made of TA6V in plate form, when it is finished by milling, grinding or machining, is coated with a layer containing molybdenum having a thickness of 150±20 μm by plasma spraying.

[0085] I.2. Hydration step

[0086] When the components were coated with a layer comprising molybdenum, the components made of TA6V in the form of plates were placed in tap water at a temperature of 80° C. to 95° C. for 24 hours.

[0087] II. Measurement of friction coefficient

[0088] Under the test conditions of 8 Hz frequency and 530 MPa contact pressure, the The wear behavior was studied by sliding between a copper alloy pin and a track made of TA6V in the presence of a type lubricant. The values ​​of the friction coefficient were measured on a tribometer.

[0089] When the surface is treated as defined in point I above, the coefficient of friction is 0.18 ( Figure 1 ).

[0090] It should be noted that the surface of TA6V subjected only to the first step of the method according to the invention as defined in point I.1 above has a friction coefficient of 0.20 ( Figure 2 ).

[0091] For comparison, a surface of TA6V covered with a layer comprising molybdenum according to the solution as defined in point I.1 has a friction coefficient of 0.35 ( Figure 3 ), which layer is subsequently covered with an organic resin layer.

[0092] In addition, the friction coefficient obtained for the surface of TA6V subjected to the treatment method defined in point I above remains stable after up to 300,000 cycles, however, under the same conditions of covering distance, starting from 60,000 cycles, the friction coefficient of the surface of TA6V coated with a layer containing molybdenum and an organic resin layer is unstable but always at a high value, i.e. greater than or equal to 0.35.

[0093] As already explained, hydration does not change the porous structure of the layer containing molybdenum, in contrast to the organic resin which blocks the pores of the layer. The pores present in the molybdenum layer act as lubricant reservoirs under the conditions of the test and therefore under the conditions of use of the metal part treated according to the method of the invention.

Claims

1. A method for improving the wear resistance of a component, the method comprising the following steps: a) depositing a layer comprising molybdenum by thermal spraying on all or part of the surface of the component; b) contacting the surface of the component having the layer comprising molybdenum with an aqueous solution at a temperature above room temperature, exceeding 30° C., for hydration; Wherein, during step (b), the duration of the contacting is between 1 hour and 54 hours, and the weight proportion of the molybdenum relative to the total weight of the layer is greater than or equal to 70%.

2. The method according to claim 1, wherein: The surface of the component is made of a material selected from the group consisting of titanium alloy, nickel alloy and austenitic stainless steel.

3. The method according to claim 1 or 2, wherein: The component is a component selected from the group consisting of: ball joint systems, piston rods, rings, gears, camshafts, valves, injection pumps, bearing housings, bearings and shafts.

4. The method according to claim 1 or 2, wherein: During said step (a), said thermal spraying used is plasma spraying.

5. The method according to claim 1 or 2, wherein: During said step (a), said layer deposited by thermal spraying mainly comprises molybdenum.

6. The method according to claim 1 or 2, wherein: During said step (b), said aqueous solution comprises only water.

7. The method according to claim 1 or 2, wherein: During said step (b), said aqueous solution comprises at least one further element besides the solvent.

8. The method according to claim 1 or 2, wherein: During said step (b), the contacting is performed in a static mode or in a dynamic mode.

9. The method according to claim 1 or 2, wherein: During said step (b), the duration of said contacting is between 5 hours and 48 hours.

10. The method according to claim 1 or 2, wherein: Prior to step (a), the method comprises a step of sandblasting the surface or a processing step.

11. A component, wherein a layer comprising molybdenum is deposited on all or part of the surface of the component according to the method of any one of claims 1 to 10 and then hydrated at a temperature above room temperature, wherein the weight proportion of molybdenum relative to the total weight of the layer is greater than or equal to 70%.

Citation Information

Patent Citations

  • Interface for adapting the friction between two nickel or nickel alloy or chromated cobalt parts moving relative to one another at high temperature

    FR3042563A1

  • Improvements in methods of coating surfaces to render them abrasion resistant

    GB2111861A

  • Friction adjustment interface between two parts made of nickel or nickel or cobalt-chromium alloy that are in relative motion against one another at high temperature

    US20170107603A1

  • Friction elements of machines subjected to heavy loads

    US3658576A

  • Wear resistant coated vehicle component and vehicle

    WO2007043961A1